IDENTIFIKASI VEGETASI DI KORIDOR SUNGAI SIAK DAN PERANANNYA DALAM PENERAPAN METODE BIOENGINEERING - Sittadewi, Euthalia Hanggari (Jurnal Sains dan Teknologi Indonesia, 2008)
The Siak river corridor has been damaged as a result of the traffic of high capacity vessels and loss of the green belt in riverside cause of the kick of waves and poisioned of the pollutants.That’s to cause damage to part of land and vegetation in the river corridor. It’s necessary that riverside’s protection. The research is identification of vegetation on the Siak river corridor between dusun Buatan and dusun Sigentil with an objective that the result of the identification can be used in application to the Bioengineering for riverside’s protection. From the identification result, there are 20 species of plants on the Siak river corridor beetwen dusun Buatan and dusun Sigentil. There are : akasia (Acasia,sp), alang – alang (Imperata cylindrica), asam payau (Acanthus ilicifolium, L), bambu kasap (Pogonatherum, sp), bambu kuning (Bambusa vulgaris), binjai (Mangifera caesia), bintaro (Cerbera manghas, L), berembang (Sonneratia, sp), jawi – jawi (Ficus, sp), keduduh (Melastoma candidum, D.Don), kelapa sawit (Elaeis guineensis), kempas (Koompasia malaccensis), manggis (Garcinia, sp), pandan (Pandanus, sp), putat (Barringtonia spicata), rengas (Glutha renghas), rumbia (Nypha fructicans,Wurmb), rumput kumpai (Hymenachne acutigluma), rumput teki (Cyperus rotundus), waru (Hibiscus tiliaceus, L). Some of the species are rengas (Glutha renghas), bintaro (Cerbera manghas, L), pandan (Pandanus, sp), keduduh (Melastoma candidum, D.Don), rumput teki (Cyperus rotundus), rumput kumpai (Hymenachne acutigluma), alang – alang (Imperata cylindrica), bambu kuning (Bambusa vulgaris), bambu kasap (Pogonatherum, sp) and rumbia (Nypha fructicans, Wurmb) can be used or have contribution in the Bioengineering application for riverside’s protection beetwen dusun Buatan and dusun Sigentil or the other segmens of the Siak river corridor have the same of phisic characteristics.